(untitled) (Journal of EAHIL, 2017)
Dear Colleagues, As the trees in Edinburgh are beginning to turn gold and red, it’s pleasant think back to summertime and the conference in Rome! I hope you had a good summer, with holidays and excursions and plenty of fun. Since this issue is focussing on the conference in Rome, I thought it would be a useful exercise to draw on the feedback that participants sent in, and look at the ideas for topics of future EAHIL events. So, having had a successful conference in 2014, where do we want to go next?